Integrating before and after crash features into measuring the effectiveness of intersection safety improvement project in Harbin - Yong-Gang Wang; Kuan-Min Chen; Yu-Long Pei; Ying Wang (Transport, 2011)
Many studies focused on the analysis of effect factors contributing to the crashes and development of crash prediction models have resulted in aggregate researches to quantify the safety effects of geometric and traffic variables and environmental concerns on the expected outcome of fatal, injury and/or property damage losses at specific locations. Crash insight regarding different locations, however, has rarely been performed. Such investigations are useful for at least two reasons. First, there is a priori need to identify high risk sites with respect to crash. Second, it is generally believed that different crash types (e.g. rear-end, angle etc.) are associated with road geometry, the environment and traffic condition, and as a result justifying the inside causes of such crashes helps with understanding and improving the specific ability to make effective countermeasures. Therefore, the objectives of this paper are to (1) demonstrate that different crash types are associated to intersections in different ways and (2) reveal that the statistics of intersection crashes may lead to greater insights considering crash occurrence and countermeasure effectiveness. This paper first divides crashes into 5 categories or types: pedestrian-involved, rear-end, head-on, angle and sideswipe crash types. Based on 3208 crashes collected on the intersections in the city of Harbin during the period of 1992–2008, distribution, overall count and the occurrence of rate features are estimated resulting in two models. The performed analysis reveals that safety improvement factors such as the presence of a signal light set, a traffic monitoring device and ITS measure have a positive association with intersection crash in different ways, suggesting that different traffic control and management aspects may be helpful in identifying specific countermeasures in the overall safety improvement project.